2018
DOI: 10.3329/dujps.v16i2.35263
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antioxidant Activity of Some Novel Benzimidazole Derivatives

Abstract: A series of 2-substituted-5-methylbenzimidazole derivatives (3a-e) were synthesized by reacting 4-methyl-1,2-phenylenediamine (1) with a number of p-substituted benzaldehydes (2a-e) in moderate yields (25.51-40.21%). The synthesized compounds (3a-e) were characterized by spectroscopic data and were evaluated for antioxidant activity using DPPH free radical scavenging assay. The compounds showed significant antioxidant activity having IC50 value of 1.054-19.05 µg/ml as compared to the standard BHT (26.96 µg/ml). Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…This might be due to the direct antioxidant properties of both compounds or the activation of antioxidant defense machinery. The antioxidant capacity and free radical scavenging properties of benzimidazole derivatives were confirmed previously [ 68 , 69 ] and were reported to be associated with their structural features [ 70 ]. Taken together, we believe that treating pepper plants with HPBI or Al−HPBI complex might reduce the development of Fusarium wilt disease in pepper plants by directly increasing the antioxidant capacity within infected plants.…”
Section: Discussionsupporting
confidence: 70%
“…This might be due to the direct antioxidant properties of both compounds or the activation of antioxidant defense machinery. The antioxidant capacity and free radical scavenging properties of benzimidazole derivatives were confirmed previously [ 68 , 69 ] and were reported to be associated with their structural features [ 70 ]. Taken together, we believe that treating pepper plants with HPBI or Al−HPBI complex might reduce the development of Fusarium wilt disease in pepper plants by directly increasing the antioxidant capacity within infected plants.…”
Section: Discussionsupporting
confidence: 70%
“…The result is hydrogen peroxide (H2O2) which is a non-radical oxidant. Furthermore, the radical Hydrogen peroxide (H2O2) will be neutralized by enzymatic antioxidants Gluthation peroxidase (GSH-Px) and catalase to be converted into water (H2O) and oxygen (O2) (Karmaker, Lira, Das, Kumar, & Rouf, 2017). Radicals Hydrogen peroxide (H2O2) can also react again with superoxide anion (O2•-) to hydroxyl radicals (OH-) called the Haber-Weiss reaction.…”
Section: Resultsmentioning
confidence: 99%
“…10i) [107][108]. Karmaker et al [109] reported the design of a series of benzimidazoles with nitro substituents which exhibited higher antioxidant than BHT. Watanabe and co-workers reported a rational design and clinical trials of novel antioxidant edaravone (3-methyl-1-phenyl-2-pyrazolin-5one) (Fig.…”
Section: Fig 9 5-hydroxypyrimidinementioning
confidence: 99%